Production of cellulase-free xylanase by Trichoderma reesei SAF3 - Kar,Sanjay (2006)
A xylanase producing fungi has been isolated from soil and identified as Trichoderma reesei SAF3. Maximum growth of the organism was found at 48 h under submerged condition in xylan containing enriched medium, whereas highest enzyme production (4.75U/mL) was recorded at 72 h. No detectable cellulase activity was noted during whole cultivation period. The partially purified enzyme hydrolyzed xylan into xylopentose and xylose. All these properties of xylanase highlighten its promising uses in industrial scale.